2001
DOI: 10.1148/radiographics.21.3.g01ma20657
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Interventional Procedures: Aspiration, Biopsy, and Catheter Drainage

Abstract: Transvaginal ultrasonographically (US) guided procedures are simple and safe and often represent the only means of access to pelvic disease. Aspiration of cystic pelvic masses and core biopsy of solid pelvic masses can be easily performed by using the transvaginal route, an endoluminal US transducer, and a needle guide. Because of concerns about false-negative diagnosis and potential tumor seeding with biopsy of primary ovarian cystic lesions, the indications for transvaginal aspiration and biopsy of ovarian a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…It may be used before the induction of ovulation in IVF programs. In addition, the use of alcohol appears to significantly reduce the symptoms associated with endometriomas, with a decreased risk of adhesion formation because the procedure is intratumoral (29) . This study demonstrated an effective remission of endometrioma volume after aspiration and the use of alcohol in all reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…It may be used before the induction of ovulation in IVF programs. In addition, the use of alcohol appears to significantly reduce the symptoms associated with endometriomas, with a decreased risk of adhesion formation because the procedure is intratumoral (29) . This study demonstrated an effective remission of endometrioma volume after aspiration and the use of alcohol in all reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…The indications for transvaginal drainage of pelvic fluid collections include both gynecologic and non-gynecologic conditions, such as simple or complex tubo-ovarian abscesses, postoperative abscesses and diverticular abscesses. In the literature, success rates close to 100% using a US-guided transvaginal approach have been reported but all the studies enrolled small populations and lacked statistical significance [62,[72][73][74][75][76][77]. More recently, Rose et al [78] studied a larger population (n=46) and reported that 3D reconstruction during the US-guided approach can add substantial information on structure and spatial resolution to optimize the initial drainage of complex fluid collections.…”
mentioning
confidence: 99%
“…Prophylactic intravenous antibiotic-therapy (cephoxitin 1g or clindamycin 1g + gentamycin 80 mg + ampicillin 1g) is mandatory. Additionally a 300 mg-dose of clindamycin each six hours for five days may be recommended (5) .…”
Section: Transvaginal and Transrectal Approachesmentioning
confidence: 99%
“…Collections and cysts must be completely drained in order to avoid hyperinfection by the rectovaginal flora (5) .…”
Section: Transvaginal and Transrectal Approachesmentioning
confidence: 99%
See 1 more Smart Citation